Cost-effectiveness analysis of 10- and 13-valent pneumococcal conjugate vaccines in Peru - Mezones-Holguin E. (2015)
This study was made possible through the financial support of the Instituto Nacional de Salud (National Institute of Health, Lima, Peru) and the PROVAC Initiative of the Pan American Health Organization (Washington, DC, USA). This study was presented at 9th International Symposium of Pneumococci and Pneumococcal Diseases, Hyderabad, India, March 2014, and supported by the National Council of Science, Technology and Technological Innovation of Peru (CONCYTEC) and International Clinical Epidemiology Network (INCLEN Trust).